Water Activity Control in PEMFC Electrical Energy System - Farid Saadaoui; Khaled Mammar; Abdaldjabar Hazzab (Majlesi Journal of Electrical Engineering, 2021)
This work is designed to study the energy management of a Proton Exchange Membrane Fuel Cell (PEMFC), which is based on the activity and management of water and its effect on the electrolyte membrane (FC) as a function of the influx of hydrogen and oxygen, by taking into account the influence of humidification on the implementation of this electrical system to avoid drying and flooding that can cause deterioration of the FC. The cell voltage and system efficiency are also influenced by current density and operating temperature, and simulation results on Matlab / simulink are discussed.